Reforma autotérmica do metano em catalisadores de Ni/CeZrO2/Al2O3 para a produção de hidrogênio - Escritori, Janaína Centenaro (2007)
In this work, nickel catalysts supported on CeO2/Al2O3 and CeZrO2/Al2O3 were investigated in reforming autothermal of methane, aiming hydrogen production. Two types of aluminas with different areas were used (Al2O3-D and Al2O3-C). Therefore, two catalysts series were prepared: one was supported on Al2O3-D, and another series supported on Al2O3-C. The characterization techniques used were BET surface area, X-Ray Diffraction (XRD), Temperature programmed reduction (TPR-H2), CO2 Temperature programmed dessorption (CO2-TPD) and a model reaction, the dehydrogenation of cyclohexane, was used to evaluate the dispersion of nickel particles. The samples supported on Al2O3-C presented larger values of BET surface areas. XRD analysis showed the formation of a CeZrO2 solid solution. TPR results showed that the presence of cerium and cerium-zirconium oxides promoted the reduction of NiO, increasing the reducibility of the respective catalysts. CO2-TPD analysis indicated the presence of basic sites and of redox sites and that both the support as well as the reduced nickel, quimissorved CO2. The catalysts supported on Al2O3-C presented better nickel dispersions, measured by dehydrogenation of cyclohexane reaction. Light-off curves showed that autothermal reforming of methane occurred by indirect mechanism, which consisted on combustion at lower temperatures, with the posterior reforming of methane by CO2 or H2O at higher temperatures. The catalytic tests of long duration presented, for the majority of the tested samples, good activity, stability and high hydrogen selectivity. CeO2 and CeZrO2 had an important role for the stability of the samples, helping in the regeneration of catalytic surface. The H2/CO ratios were around 2.5 for all the samples, which is a good value for the autothermal reforming of methane. The samples supported on Al2O3-C had presented higher H2/CO ratios. Ni/CeZrO2/Al2O3-C catalyst showed the best activity and this performance is coherent with the results of TPR, which presented higher reduticibility and higher nickel dispesion.